Ba(ZrxTi1−x)O3 thin films for tunable microwave applications. (July 2015) - Jinwoong, Kim; Shima, Hiromi; Yamamoto, Takashi; Yasui, Shintaro; Funakubo, Hiroshi; Yamada, Tomoaki; Nishida, Ken
Abstract: Ba(Zr x Ti1− x )O3 (BZT) thin films were deposited on (100)MgO substrates by RF-magnetron reactive sputtering using metal targets. Coplanar capacitor test structure with Pt/Au electrode based on BZT/MgO layer was fabricated by sputtering, photolithography, and etching processes. 500-nm-thick BZT thin films for high frequency performance showed a single perovskite phase and a high crystallinity on the MgO substrate with only a (001)/(100) orientation at an optimum deposition conditions. The BZT films had a stoichiometric Ba/Ti ratio and epitaxially grew on the MgO substrate. They showed a dense microstructure without cracks or voids. Dielectric properties of BZT thin film ( x =0.26) showed little dispersion at 1–18 GHz. Moreover, low frequency dielectric properties have been characterized using coplanar capacitor structures in a temperature range of −180 to 120 °C. This film showed the high temperature stability of capacitance and loss tangent. These results indicated that we succeeded in depositing high-quality and potentially tunable ferroelectric BZT films for high-frequency applications by RF-magnetron reactive sputtering using metal targets.